Faktor Yang Berhubungan dengan Perilaku Seksual Pranikah pada Remaja SMAN 1 Kelam Permai Kabupaten Sintan Provinsi Kalimantan Barat - Gaung Eka Ramadhan; Ajat Sudrajat (Yayasan Literasi Sains Indonesia, 2022)
Premarital sexual behavior, especially in adolescents, is very worrying about the impact of venereal disease, HIV/AIDS and pregnancy out of wedlock. This study aims to determine the factors associated with Premarital Sexual Behavior in Adolescent Senior High School 1 Kelam Permai, Sintang Regency, West Kalimantan Province. The design of this study used quantitative analytic with cross-sectional sectional method completed qualitatively with respondents were class X students, and XI from SMAN 1 Kelam Permai a total of 170 respondents. Data analysis used uni variate analysis and bivariate analysis. The results showed a significant relationship between premarital sexual behavior with knowledge p-value: 0.001 and OR value of 3.085, p-value attitude: 0.001 and OR value of 5.797, religious observance of p-value: 0,000 and OR value of 8.036, self-control p-value : 0.002 and an OR value of 6.077 and access to pornographic media p-value: 0.001 and an OR value of 7.635. Research Indicated by informers includes the lack of knowledge of premarital sexual behavor, supportive neighborhoods and local habits, the abuse of media by students to obtain pornographic content. Then approaches such as counseling and seminars on the dangers of sex and sexual violence need to be done.